PERAN WORLD FOOD PROGRAMME (WFP) MELALUI FOOD ASSISTANCE FOR ASSETS (FFA) DALAM MENANGANI KERAWANAN PANGAN DI SUDAN SELATAN 2016 - 2020 - Edgina Aisyah Saphira, (2021)
World Food Programme's (WFP) Food Assistance for Assets (FFA), offers humanitarian aid in a long term food assistance form. FFA aims to improve household assets by building resilience to climate disaster that cause loss to national food crop and livestock productivity, in which 95% of people in South Sudan, depend on climate-sensitive sectors, including agriculture, forestry resources and fisheries for their livelihoods. Through this thesis, the author analyzes WFP's role in South Sudan using FFA program throughout 2016 - 2020 to overcome South Sudan's food insecurity using qualitative method. This analysis emphasizes that Food Assistance for Assets (FFA) is given to reach SDG number 2 (Zero Hunger) and SDG number 17 (Partnerships for The Goals) in the middle of climate disaster and complex local political-armed conflict that causes national food aid dependent for years. WFP's role includes working as an international organization that focuses on delivering humanitarian aid and cooperate with local authorities to implement the assets-based program as a part of an overall solution to end world hunger, that, in fact keeps growing in South Sudan until today.